Differential diagnosis and therapeutic approaches to cough syndrome - A. A. Bova; S. M. Metelskiy; D. Y. Ruzanov; E. I. Davidovskaya; T. A. Nekhaychik (Military Medicine, 2026)
Cough is one of the most common symptoms experienced by a general practitioner and a general practitioner. The greatest difficulties for practicing physicians are caused by cases of chronic cough and its complicated course. The range of diseases and pathological conditions accompanied by cough symptoms is extremely wide. This requires both deep theoretical knowledge and practical experience from the clinician in choosing a rational diagnostic search algorithm and optimal therapeutic tactics. This article is devoted to the problems of pathogenesis, classification, diagnostic approach and therapeutic tactics in cough syndrome.